2019
DOI: 10.3390/computers8020039
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Innovation: Case of Co-Design of Cabins in Mobile Work Machine Industry

Abstract: This paper describes the development of using virtual reality for work content in one application area over a decade. Virtual reality technology has developed rapidly; from walk-in CAVE-like virtual environments to head-mounted displays within a decade. In this paper, the development is studied through the lens of diffusion of innovation theory, which focuses not only on innovation itself, but also on the social system. The development of virtual technology is studied by one case, which is cabin design in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Over time, extensive literature has developed on DOI, and this framework has been applied to numerous contexts, such as education, public health, marketing, communications and organizational behavior. Ellman and Tiainen (2019) studied the development of VR usage in the work context through the lens of DOI, investigating not only the technological aspect but also the economic and social aspects of VR adoption. They showed that hardware and software costs declined rapidly from 2006 to 2016 (Ellman and Tiainen, 2019), and the benefits of VR became more apparent, thus attracting more users.…”
Section: Diffusion Of Innovation Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Over time, extensive literature has developed on DOI, and this framework has been applied to numerous contexts, such as education, public health, marketing, communications and organizational behavior. Ellman and Tiainen (2019) studied the development of VR usage in the work context through the lens of DOI, investigating not only the technological aspect but also the economic and social aspects of VR adoption. They showed that hardware and software costs declined rapidly from 2006 to 2016 (Ellman and Tiainen, 2019), and the benefits of VR became more apparent, thus attracting more users.…”
Section: Diffusion Of Innovation Theorymentioning
confidence: 99%
“…Ellman and Tiainen (2019) studied the development of VR usage in the work context through the lens of DOI, investigating not only the technological aspect but also the economic and social aspects of VR adoption. They showed that hardware and software costs declined rapidly from 2006 to 2016 (Ellman and Tiainen, 2019), and the benefits of VR became more apparent, thus attracting more users. It is conceivable that a similar pattern of diffusion will occur with VR adoption in the meetings and events context.…”
Section: Diffusion Of Innovation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This is a good testing case since it is a complex and large model that can provide better understanding of the applicability of dynamics simulation tools and the factors that affect real-time simulation. Moreover, mobile machine prototyping usage with VR technology has been a research focus in the last decades, particularly in Finnish industry (Ellman and Tiainen, 2019), due to several fundamental factors involved in cabin prototyping design: ergonomics, visibility, functionality, safety and industrial design (Ellman et al, 2009;Tiainen et al, 2011). The harvester CAD model consists of 3298 solids assembled in a main assembly file, representing individually each part of the machine and their static relations positions.…”
Section: Cad Modelmentioning
confidence: 99%
“…The designer may get intuitive access to various mechanical components, which is particularly advantageous for design modifications with existing digital models, contributing to cost savings and sustainable development. During a decade, VR technology has developed rapidly, resulting in low operational cost and fast process time (Ellman and Tiainen, 2019). This immersive technology has been adopted by many industries in their workflow, because of the advantages that they offer to design practices (Berg and Vance, 2017).…”
Section: Introductionmentioning
confidence: 99%